2013
DOI: 10.1016/j.bbamem.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior and domain size in sphingomyelin-containing lipid bilayers

Abstract: Membrane raft size measurements are crucial to understanding the stability and functionality of rafts in cells. The challenge of accurately measuring raft size is evidenced by the disparate reports of domain sizes, which range from nanometers to microns for the ternary model membrane system sphingomyelin (SM)/1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC)/cholesterol (Chol). Using Förster resonance energy transfer (FRET) and differential scanning calorimetry (DSC), we established phase diagrams for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
153
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(172 citation statements)
references
References 73 publications
17
153
1
1
Order By: Relevance
“…Along a tieline the fraction of each coexisting phase is known. Currently, the majority of published phase diagrams describe neutral lipid mixtures (36)(37)(38)(39)48). No published data are available with ternary phase diagrams containing PC/PS/Chol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Along a tieline the fraction of each coexisting phase is known. Currently, the majority of published phase diagrams describe neutral lipid mixtures (36)(37)(38)(39)48). No published data are available with ternary phase diagrams containing PC/PS/Chol.…”
Section: Resultsmentioning
confidence: 99%
“…One previous study found a nonphysiological enrichment of cholesterol in virions compared to the cellular plasma membrane (33); however, a more thorough study found no significant enrichment in cholesterol (35). Additionally, in model membranes with coexisting raft and non-raft domains at a physiological cholesterol mole fraction of 0.35 to 0.4, cholesterol is present at similar levels in the coexisting domains (36)(37)(38)(39). Also, under some conditions Gag is found in cold detergent-resistant membranes (DRMs) along with raft markers (40)(41)(42)(43).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…These constituents are thought to segregate dynamically into nanoscale lateral domains called lipid rafts, which influence vital bioactivity such as signaling events, transport across biological membranes, and regulation of the activity of membrane proteins. 1,2,3,4,5 Due to the complexity of cell membranes, numerous studies have mimicked raft domain properties and phase state using simple model systems comprised of a high melting point (T M ) lipid, a low T M lipid, and sterol. 2,6,7,8 Such ternary mixtures can form coexisting liquid ordered (L o ) / liquid disordered (L d ) phases analogous to liquid-liquid immiscibility in cellular membranes and raft formation.…”
Section: Introductionmentioning
confidence: 99%